PERANCANGAN RUMAH SUSUN DENGAN PENDEKATAN ARSITEKTUR TROPIS DI MEDAN - Sibarani, Paterson H.P.; Angelina, Jasmine (LPPM ISTP, 2023)
The house is a building, where humans live and carry out their lives. Besides that, the house is also the place where the socialization process takes place when an individual is introduced to the norms and customs that apply in a society. Development in big cities is growing rapidly, one of them is Medan City. The development of the city of Medan to date and the increasing population has caused the need for housing and settlements to increase. Vertical housing development in the form of flats is an alternative that must be developed to overcome the population explosion, low-income communities and limited land which makes land prices expensive.